KEBUTUHAN DIKLAT PELAUT III DITINJAU DARI ASPEK TOOL’S DAN ENGINEERING - Frenki Imanto (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2019)
The purpose of this research is to get a reference on facilities and infrastructure needed in the learning process for 3rd officers of Engineering Department in terms of equipment and engineering aspects in table form. The table is expected as guidance for Education and Training Institutions especially Engineering Department. It means as quality standard for Education and Training Institutions to fulfil the requirements, such as laboratories and simulators. Laboratories and simulators are very expensive, so their existence are limited. Many private Education and Training Institutions have to join public Education and Training Institutions to solve this problem, one of them is Politeknik Pelayaran Surabaya.  The first stage is planning. It is consist of determining the variables, population and sampling, research location also determining the data collection technique along with the instrument. The second stage is data collecting. To collect the data, the researcher uses the instrument prepared at planning stage. The third stage is analysing the datum. Based on the datum above, the result of 3rd officers’ training needs based on equipment and engineering are 1) the equipment needed is 15 units and 2) the the engineering aspect needed is 9 units. The results are significant with “The List 3rd Officers’ Training Needs based on Equipment and Engineering” table.Keywords: Needs,Training, Equipment, EngineeringPenelitian ini bertujuan untuk mendapatkan acuan kebutuhan sarana dan prasarana yang seharusnya tersedia dalam proses pembelajaran Diklat Pelaut III Jurusan Teknika ditinjau dari aspek tool’s dan engineering dalam bentuk tabel. Tabel tersebut diharapkan dapat digunakan sebagai pedoman evaluasi bagi penyelenggara Diklat Pelaut III Jurusan Teknika guna memenuhi tuntutan penyelenggarakan pendidikan dan pelatihan yang berkualitas sesuai dengan standar, pemecahan permasalahan pemakaian beberapa laboratorium dan simulator di Politeknik Pelayaran Surabaya yang cukup rendah dan adanya instansi penyelenggara pendidikan dan pelatihan kepelautan yang fasilitasnya terbatas yang ditandai dengan adanya kegiatan praktek tambahan bagi peserta diklat yang dikelola oleh pihak swasta di instansi diklat yang dikelola oleh pemerintah.Tahapan analisis yang digunakan yaitu perencanaan, pengumpulan data dan analisis data. Pada tahap pengumpulan data yang dilakukan adalah mengumpulkan data dengan menggunakan instrumen yang telah disusun pada tahap perencanaan. Sedangkan pada tahap analisis yang dilakukan adalah (1) memilah data untuk dikelompokkan kedalam data primer dan sekunder, dan (2) menganalisis data dengan pendekatan deskriptif untuk mengolah data guna menghasilkan gambaran fenomena atau keadaan yang ada.Kata kunci : Kebutuhan, Diklat, Tool’s, Engineering